Persepsi Terhadap Nikah Sirri Kasus Masyarakat Desa Sinarrancang, Kecamatan Mundu, Kabupaten Cirebon - Ismail Zubir (Analisa: Journal of Social Science and Religion, 2011)
This study aims to find out the perception of people in Sinarrancang, Mundu, Cirebon, West Java, on nikah sirri (“secret” marriage). Using qualitative approach the study reveals that in their opinion nikah sirri mean  nikah “kyai”, it is a marriage by ulama and  has become a long hereditary tradition. According to  fiqih munakahat (a branch of Islamic law which studies  about  marriage) this kind of marriage is legitimate because it meets the conditions and requirements of marriage. According to positive law, however,  such  marriage is illegal for not being registered at KUA (a governmental institution which administers Muslim marriage). In order to change their perception on nikah sirri, it needs to socialize UU No. 1 Tahun 1974 continuously. KUA’s service to people has to be addressed so that its accountability  and responsibility could run effectively; and more importantly the draft  of   Religious  Courts Law Materials that would provide punishment for those conducting nikah sirri do not contradict with Islamic law.